Acute effect of technique modification training on 180° change of direction performance and kinematics in adolescent male soccer players - Hayato Nakamura; Daichi Yamashita; Daichi Nishiumi; Naoto Nakaichi; Norikazu Hirose (Frontiers in Sports and Active Living)
IntroductionChange of direction (COD) maneuvers are frequently performed during soccer games and are critical for performance. Adolescent players often display immature COD maneuvers, suggesting that COD technique modification training may be a more effective approach for adolescent athletes. This study investigated the acute effects of COD modification training on COD performance and kinematics in male adolescent soccer players.MethodsTwenty-nine male junior high school soccer players participated in this study and were divided into two groups: 16 players underwent 15-min COD technique modification training (COD group), while 13 players engaged in 15-min linear sprint training. The participants performed Pro-Agility and 20-m sprint tests before and after the intervention, and the total times were measured. COD deficit (CODD) was calculated as the difference between these times. Center of mass (COM) velocity and trunk and lower limb kinematics were computed from three-dimensional kinematic data collected during the Pro-Agility test using a markerless motion capture system. Each section of the Pro-Agility test was divided into acceleration and deceleration phases based on the COM velocity; Stop marks the moment of direction change. Two-way (group and time) mixed ANOVA was conducted with Bonferroni corrections for post-hoc comparisons.ResultsNo significant interactions were observed in the total time of the Pro-Agility test, CODD, 20-m sprint time, or average acceleration and deceleration in each phase (p > 0.05). On the other hand, the COD group showed significant interactions and improvements in average deceleration from final foot (FF) contact to Stop (p = 0.012, g = 0.639), penultimate foot hip flexion angle at Stop (p = 0.042, g = 0.496), COM-FF horizontal distance at Stop (p = 0.008, g = 0.650), and FF ground contact time (p < 0.001, g = 0.803).ConclusionA 15-min COD technique modification training led to partial, immediate improvements in kinematic parameters among adolescent soccer players but did not enhance overall COD performance or acceleration/deceleration ability.